2005
DOI: 10.1007/s10641-004-7097-6
|View full text |Cite
|
Sign up to set email alerts
|

Early life history and settlement of the slender filefish, Monacanthus tuckeri (Monacanthidae), at Calabash Caye, Turneffe Atoll, Belize

Abstract: SynopsisWe examined early life history traits and patterns of settlement of the slender filefish, Monacanthus tuckeri, at Calabash Caye, Turneffe Atoll, Belize. A settlement peak was evident at the new moon, and no settlement occurred at the full moon. However, settlement rates at the quarter moons could not be estimated due to sampling gaps. Many reef fishes show new moon settlement peaks, so M. tuckeri shares some characteristics with the primarily perciform species on coral reefs. Pelagic larval duration wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…() recently reviewed otolith‐based age estimation for N. ayraud and emphasized however, the limited precision and accuracy of previous results based on age estimation using vertebrae. Otolith‐based studies have also been successfully conducted on early life stages and juveniles of S. hispidus (Rogers et al., ), Rudarius ercodes (Jordan & Fowler 1902) and Paramonacanthus japonicus (Tilesius 1809) (Kawase & Nakazono, ) and Monacanthus tuckeri (Bean 1906) (Ben‐David & Kritzer, ). Annual increment deposition has been reported in sagittal otoliths of the monacanthid species Meuschenia australis (Donovan 1824) , Penicipelta vittiger (Castelnau 1873) and N. ayraud (Barrett, ; Miller et al., ), suggesting that this pattern occurs generally in the group.…”
Section: Introductionmentioning
confidence: 99%
“…() recently reviewed otolith‐based age estimation for N. ayraud and emphasized however, the limited precision and accuracy of previous results based on age estimation using vertebrae. Otolith‐based studies have also been successfully conducted on early life stages and juveniles of S. hispidus (Rogers et al., ), Rudarius ercodes (Jordan & Fowler 1902) and Paramonacanthus japonicus (Tilesius 1809) (Kawase & Nakazono, ) and Monacanthus tuckeri (Bean 1906) (Ben‐David & Kritzer, ). Annual increment deposition has been reported in sagittal otoliths of the monacanthid species Meuschenia australis (Donovan 1824) , Penicipelta vittiger (Castelnau 1873) and N. ayraud (Barrett, ; Miller et al., ), suggesting that this pattern occurs generally in the group.…”
Section: Introductionmentioning
confidence: 99%
“…Peak ingress of postlarval gags occurred predominantly in April and May near new moons. Peaks in postlarval settlement of other reef fishes have been shown to coincide with new moon periods (Victor 1986;Walsh 1987;Wilson 2001;Watson et al 2002;Tzeng et al 2003;Ben-David and Kritzer 2005). In South Carolina, Keener et al (1988) identified peak ingress of gags as occurring on nighttime flood tides in April and May, and those authors noted that temporal variability in ingress corresponded to temporal patterns in back-calculated hatch dates.…”
Section: Development and Test Of The Postlarval Gag Abundance Indexmentioning
confidence: 99%
“…Alternatively, artificial settlement substrata have long been used to monitor the larval supply of invertebrates over large areas, because they provide a continuous estimate of recruitment with minimal cost and effort (Young, 1990; Rabalais et al ., 1995). Passive collectors have recently been adapted to monitor recruitment of temperate and tropical nearshore reef fishes by capitalizing on the strong affinity of competent fish larvae for physical structures (Findlay & Allen, 2002; Steele et al ., 2002; Ammann, 2004; Ben‐David & Kritzer, 2005; Valles et al ., 2006).…”
Section: Generalized Linear Model Of Sebastes Melanops Recruitment Dumentioning
confidence: 99%
“…A recent study concluded that a passive collector known as the ‘standard monitoring unit for the recruitment of fishes' (SMURF) is an accurate and efficient tool for indexing the relative rates of delivery of competent juvenile fishes to temperate rocky reef habitats (Ammann, 2004). Subsequent studies using SMURFs have adapted this experimental design to a variety of different species, geographic locations and research goals (Ammann, 2001, 2004; Ben‐David & Kritzer, 2005; Valles et al ., 2006). Comparisons among collectors, however, depend on maintaining similar attractiveness to recruits.…”
Section: Generalized Linear Model Of Sebastes Melanops Recruitment Dumentioning
confidence: 99%